Assessment of microclimate and gaseous pollutants in dairy and pig sheds in an organised farm - DIVYALAKSHMI, D; KUMARAVELU, N; MASILAMONI RONALD, B SAMUEL; SUNDARAM, S MEENAKSHI; VANAN, THANGA THAMIL (The Indian Journal of Animal Sciences, 2017)
Intensive livestock production is one of the major sources of atmospheric emissions of greenhouse gases. The microclimate of livestock sheds also influences the productivity and shelf-life of livestock products. The present study assessed the gaseous pollutants and microclimate in dairy and pig sheds in an organised farm. Three types of livestock buildings, viz. dairy cow, pig fattener sty and farrowing pen were selected for the study purpose. Microclimatic data was recorded daily during rainy, winter and summer seasons periodically. Indoor gaseous pollutants, viz. carbon dioxide (CO2), ammonia (NH3) and methane (CH4) were recorded using multi gas monitor. The assessed THI values were higher than the ideal value of 72 in all the livestock sheds irrespective of the seasons. With regards to gaseous pollutants, CO2 and NH3 emissions were less in the afternoon when compared to morning sessions in contrast to CH4 which was higher in afternoon sessions in all the sheds. All the three gaseous pollutants were within the recommended threshold limit level.